Adenoid cystic carcinoma of the salivary glands: a pilot study of potential therapeutic targets and characterization of the immunological tumor environment and angiogenesis - Michaelides, Ioannis; Künzel, Julian; Ettl, Tobias; Beckhove, Philipp; Bohr, Christopher; Brochhausen, Christoph; Mamilos, Andreas (European archives of oto-rhino-laryngology and head & neck, 2023)
Adenoid cystic carcinoma (ACC) is a rare type of cancer commonly occurring in salivary glands. It is characterized by slow but infiltrative growth, nerve infiltration and overall poor prognosis, with late recurrence and distant metastasis. The treatment of ACC is still limited to surgery and/or (adjuvant) radiotherapy. Till now no promising systemic therapy option exists. However, various studies deliver promising results after treatment with anti-angiogenetic agents, such as anti-EGFR-antibody Cetuximab or Tyrosinkinase inhibitor Lenvatinib.
Online veröffentlicht: 1. März 2023
Gesehen am 21.08.2024